HELMINTH PARASITES OF ANISOTREMUS SCAPULARIS (TSCHUDI, 1846) (PERCIFORMES: HAEMULIDAE) "PERUVIAN GRUNT" ACQUIRED AT THE FISHING TERMINAL OF VILLA MARIA DEL TRIUNFO, LIMA, PERU - Chero, Jhon (2014)
Peruvian Grunt Anisotremus scapularis Tschudi, 1846 (Haemulidae) is a carnivorous marine benthopelagic fish species distributed between Ecuador and Chile. The aim of this study was to identify helminths parasitizing A. scapularis in the Peruvian coast. 20 specimens of A. scapularis were acquired between July and October 2013 from the Fishing Terminal of Villa Maria del Triunfo, Lima, Peru. Monogeneans and flukes were collected, fixed, preserved in 70% alcohol, colored with carmine Acetic of Semichon, Trichrome of Gomori and mounted in Canada balsam. Nematodes were fixed in hot 70% alcohol and made more transparent in a mixture of alcoholphenol. The following ten species of parasites were identified: Monogenea: Encotyllabe antofagastensis, Choricotyle scapularis, Neobivagina chita and Mexicana sp.; Trematoda: Lobatostoma anisotremun, Lasiotocus sp. and Proctoeces sp.; Acanthocephala: Profilicollis altmani and Gorgorhynchus sp.; Nematoda: Philometra sp. and Proleptus carvajali. The monogeneans C. scapularis and E. antofagastensis and the digenean Lasiotocus sp. and Proctoeces sp. represent new geographical records to the Peruvian helminthological fauna and A. scapularis is a new host record for Gorgorhynchus sp., Philometra sp. and P. carvajali in Peru.